Limited income and its impact on the family economically and socially - AL- Hasani, Aziz Ahmed Saleh Nasser (Journal of Humanities & Social Sciences, 2019)
This research aims to clarify the limited income of the research sample members. The family also has a variety of economic resources and is adequate for the family. To illustrate the economic and social effects of limited income on families. As well as assessing the economic and social situation of low- income people. Provide solutions that contribute to addressing the causes of low economic income for low- income people. To achieve the objectives of the research, the descriptive approach was used to interview a certain segment of the low- income community as a sample of research workers in the government sector, in the Directorate of 70 in Sana'a. The sample size was 68 (researched) heads of households.Through the results collected from the field research and analysis area, a number of general results were reached, the most important of which is: the majority of the families of the members of the sample did not depend on a single economic source, but depended on additional economic sources multiple and varied, confirmed by 63% of the total sample, this indicates that A family that does not fully depend on the monthly salary of the state. However, despite the multiplicity of these sources, they are not enough for the individual and his family, because of the high prices. The results also showed that the majority of the families of the sample members could not save any cash for any emergency they might face, accounting for 82% of the total sample.
Keywords: income; effects; family